Monetary policy and wandering overinvestment cycles in East Asia and Europe - Gunther Schnabl (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2017)
The paper analyses the role of monetary policy for cyclical movements of investment and asset markets in East Asia and Europe based on a Mises-Hayek overinvestment framework. It is shown how the gradual global decline of interest rates has triggered wandering overinvestment cycles in Japan, Southeast Asia and China. Similarly, it is shown how a one-size monetary policy within the European Monetary Union has not preserved the European Monetary Union from idiosyncratic economic development and crisis because of uncoordinated fiscal policies. With monetary policy crisis management being argued to impede financial and economic restructuring, a timely exit from ultra-expansionary monetary policies is recommended for both East Asia and Europe to reconstitute economic stability and growth.
Keywords: E52; E58; F42; E63; 330; Hayek; Mises; East Asia; European Monetary Union; monetary overinvestment theory; fiscal policy; asymmetric shocks; secular stagnation